Exploring Lesson Plans Through Learning Objectives Written by English Teachers - Jaul Fadoli (Journal of Education and Teaching Learning, 2022)
Writing instructional objectives on lesson plan should not be missed. It exactly becomes a must. This present study aimed to intently explore English teachers’ lesson plans through learning objective theory. This research employed a descriptive qualitative research design. The documentations were five lesson plans primarily gained from ayoguruberbagi.kemdikbud.go.id. The data were purposively selected with different topics and teachers. The researcher identified the learning objectives one by one. Those were then analyzed using Dick, Carey and Carey and Bloom’s theory to be categorized into three items namely CN (condition), B (behavior) and CR (criteria). The findings revealed that two among five English teachers still have inadequacy in case of creating objectives which comprises the completeness of CN (condition), B (behavior) and CR (criteria). Then, condition was found as the lowest aspect. However, all teachers had fully applied observable verbs on their learning objectives. Thus, it is required for the teachers to pay more attention to those three existences as well as the selection of verbs before designing learning objectives